Basal Ganglia Circuits Underlying the Pathophysiology of Levodopa-Induced Dyskinesia - Barroso Chinea, Pedro; Bezard, Erwan (Frontiers in Neuroanatomy, 2010)
Involuntary movements or dyskinesia, represent a debilitating complication of levodopa therapy for Parkinson's disease. Dyskinesia is, ultimately, experienced by the vast majority of the patients. Despite the importance of this problem, little was known about the cause of dyskinesia, a situation that has dramatically evolved in the last few years with a focus upon the molecular and signaling changes induced by chronic levodopa treatment. Departing from this, we here review the progress made in functional anatomy and neuroimaging that have had a tremendous impact on our understanding of the anatomo-functional organization of the basal ganglia in Parkinsonism and dyskinetic states, notably the demonstration that dyskinesia are linked to a pathological processing of limbic and cognitive information.